Diphtheria Investigation in Buranga Village of Central Sulawesi, Indonesia - Asriani, Nia; Wahyuni, Chatarina Umbul; Hadi, Supaat Setia (Health Notions, 2018)
Diphtheria is still a health problem because it still often causes outbreaks and causes death. All ages can be exposed to diphtheria but most attack children who are not immunized. The case of diphtheria in Central Sulawesi is a rare case. Even in 2015 and 2016 there was no reported diphtheria event but in 2017 there was reported suspect diphtheria. The purpose of this study was to conduct an epidemiology investigation and find additional diphtheria cases in Parigi Moutong District. This was a descriptive study with observation and interview method. Primary and secondary data were collected. Secondary data were obtained from surveillance data and investigation results while the primary data were obtained from interviews on reported probable diphtheria case.No additional cases of diphtheria were found in Parigi Moutong District. The reported case in May 2017 was an 11-year-old primary school student. The presence of diphtheria typical symptoms (bullneck and pseudomembrane) were found on clinical examination. The patient have heart problems before given anti-diphtheria serum by health officer. However, the culture examination showed negative results. The result was allegedly due to errors in the culture examination procedure performed by health officer. Index case or chains of diphtheria transmission cannot be certainly determined, but we suspected the patientâs mother to be the carrier based on history of travelling to diphtheria endemic area. There was 1 probable diphtheria case in Ampibabo Subdistrict of Parigi Moutong District. Training to increase the capacity of health workers in diphtheria management was needed.